(untitled) (Medico Legal Update, 2021)
Background: Ventral hernias result from weakness in the musculofascial layer of the anterior abdominal wall. Ventral hernia can be operated through open or laparoscopic approach. Moreover, there are various options available for mesh placement during the repair. We here report our experience in surgical management of ventral hernias along with review of published literature along with laparoscopic repair of ventral hernias. Method: It was a retrospective study of patients who were operated for ventral hernias over a period of 4 years in a teaching hospital of Vadodara SBKS research institute Dhiraj Hospital. All patients irrespective of age and sex were included. All patients were evaluated by obtaining proper history and performing detailed physical examination and routine blood investigations. Various intra operative and postoperative parameters were observed and reported. Conclusions: The ventral hernia repair can be done by open and laparoscopic technique. Each has its own advantages and disadvantages. There is no conclusively guidelines about the superiority of one technique over the other and also no conclusively guidelines for the proper position of mesh placement. The clear advantages of open technique is avoidance of general anesthesia in many cases (as many ventral hernia repairs can be done under local anaesthesia), lesser learning curve, cheap meshes can be used, easy to learn, no requirement of any sophisticated instruments or OT setup and trained staff. The disadvantage of laparoscopic technique includes the requirement for general anaesthesia (as many ventral hernias can be performed with local anaesthesia in open technique), need to transverse the abdominal cavity, prolonged learning curves, requirement of costly meshes and sophisticated equipment and technical staff. However, laparoscopy has advantage over open hernia repair in terms of reduced postoperative pain, decreased postoperative complications, reduced length of hospital stays, less time for return to normal activity and bettercosmesis.